Radiotherapy in the management of large childhood hemangiomas. - Schiebe, M.E.; Hoffmann, W.; Rebmann, H.; Kortmann, R.D.; Bamberg, M. (European Journal of Pediatric Dermatology, 1997)
Hemangiomas are common childhood anomalies. Their biological behavior is characterized by spontaneous involution in most cases and therefore a "wait and see" policy is indicated. However, in case of significant complications, therapeutical intervention is necessary. We describe a case of a large childhood hemangioma with severe complications treated successfully by radiotherapy and discuss the different treatment modalities in the management of hemangiomas. Conclusion: the major indication for irradiation in childhood hemangiomas is the treatment of lesions with functional complications in which alternative therapies have failed.